Arene Ru(II) Complexes with Difluorinated Ligands Act as Potential Inducers of S-Phase Arrest via the Stabilization of c-myc G-Quadruplex DNA - Liang Zeng; Chanling Yuan; Jing Shu; Jiayi Qian; Qiong Wu; Yanhua Chen; Ruzhen Wu; Xiaoming Ouyang; Yuan Li; Wenjie Mei (Molecules, 2022)
Here, a series of half-sandwich arene Ru(II) complexes with difluorinated ligands [Ru(η6-arene)(L)Cl] (L1 = 2-(2,3-difluorophenyl)imidazole[4,5f][1,10]-phenanthroline; L2 = 2-(2,4-difluorophenyl)imidazole[4,5f][1,10]-phenanthroline; arene = benzene, toluene, and p-cymene) were synthesized and characterized. Molecular docking analysis showed that these complexes bind to c-myc G-quadruplex DNA through either groove binding or π–π stacking, and the relative difluorinated site in the main ligand plays a role in regulating the binding mode. The binding behavior of these complexes with c-myc G-quadruplex DNA was evaluated using ultraviolet–visible spectroscopy, fluorescence intercalator displacement assay, fluorescence resonance energy transfer melting assay, and polymerase chain reaction. The comprehensive analysis indicated that complex 1 exhibited a better affinity and stability in relation to c-myc G-quadruplex DNA with a DC50 of 6.6 μM and ΔTm values of 13.09 °C, than other molecules. Further activity evaluation results displayed that this class of complexes can also inhibit the growth of various tumor cells, especially complexes 3 and 6, which exhibited a better inhibitory effect against human U87 glioblastoma cells (51.61 and 23.75 μM) than other complexes, even superior to cisplatin (32.59 μM). Owing to a befitting lipophilicity associated with the high intake of drugs by tumor cells, complexes 3 and 6 had favorable lipid-water partition coefficients of −0.6615 and −0.8077, respectively. Moreover, it was found that complex 6 suppressed the proliferation of U87 cells mainly through an induced obvious S phase arrest and slight apoptosis, which may have resulted from the stabilization of c-myc G-quadruplex DNA to block the transcription and expression of c-myc. In brief, these types of arene Ru(II) complexes with difluorinated ligands can be developed as potential inducers of S-phase arrest and apoptosis through the binding and stabilization of c-myc G-quadruplex DNA, and could be used in clinical applications in the future.